The Relationship Between Ecological Intelligence and Community Empowerment in The Development of Environmental Law in Indonesia - Mella Ismelina Farma Rahayu; Anthon Freddy Susanto (Fakultas Hukum, Universitas Warmadewa, 2025)
A severe ecological crisis will occur if a group of humans exploit nature at will without heeding the applicable rules. This condition will endanger human survival. As a result, there will be environmental damage such as air, water and soil pollution. Environmental damage that occurs now is not only local, regional and national but already global. Damage that ultimately causes harm to human life and welfare itself. In addition to causing a decrease in the carrying capacity and capacity of the environment for human life and other creatures. Ecological intelligence and community empowerment play a very important role, especially in maintaining the sustainability and sustainability of the environment, through sensitivity, awareness, understanding, and critical thinking, it is expected to overcome the problems of environmental law issues while forming environmental ethics. This research uses a legal philosophy approach, namely reviewing the nature of ecological intelligence and its relation to community empowerment in the development of Environmental Law in Indonesia, as a support, a conceptual approach is used, namely by bringing up objects of interest in this research and presenting relevant concepts to be discussed. The text criticism method is also used as an analytical knife to conduct an examination, and provide reinforcing arguments. Through ecological intelligence it can understand the issues and problems of environmental law from the perspective of ecological balance and sustainability, understand the principles of ecology. Encourage critical thinking, creative problem solving and apply legal knowledge to new situations. Assess the impact or effect of human actions and applying technology on the environment. Provide care, empathy and respect for others and other living things. Appreciate differences in backgrounds, motivations, intentions in interacting according to a perspective of mutual respect for the value of cooperation; Committed to equality, justice, inclusiveness, and respect for all people, and able to adapt to the legal system both and that is the essence of Critical Legal Empowerment.